Synthesis and analysis of capsule shape Ag-decorated ZnO for semi-transparent dye sensitized solar cell - Anupam Agrawal; Shahbaz Ahmed Siddiqui; Amit Soni; Ganesh D. Sharma (Discover Applied Sciences)
Abstract The dye-sensitized solar cells (DSSCs) are widely researched photovoltaic (PV) technology due to their distinctive features such as adjustable design like variety of colour and transparency option, light in weight, flexible, work in low light situation and short energy pay + back time PV device. These features make them attractive for building-integrated (BIPV) and automobiles, as well as interior and portable lighting systems. In this work, the synthesis of zinc oxide (ZnO) and silver decorated ZnO (Ag-ZnO) and their application in DSSC have been investigated. For the synthesis of ZnO and Ag-ZnO, inexpensive and versatile chemical co-precipitation method was used. The X-ray diffraction (XRD), UV–Visible (UV–Vis), and scanning electron microscopy (SEM) were utilized to characterize synthesized ZnO and Ag-ZnO. These synthesized materials were employed in DSSC as n-type layer in conjugation with ruthenium based dye (N719). The PV parameters of ZnO and Ag-ZnO based DSSC was obtained by current–voltage measurement. The result showed that the power conversion efficiency (PCE) of Ag-ZnO (5.42%) based DSSC was improved as compared to pure ZnO based DSSC (4.98%). We have also elaborated the colour & transparency expression in detail, and Average Visible Transmittance (AVT) of synthesized ZnO (31.37%) & Ag-ZnO (26.60%) based DSSC are presented. Graphical abstract